Efektivitas Pembelajaran Perpajakan dalam Meningkatkan Kompetensi Mahasiswa Akuntansi - Putri Sonya Aulia; Anissa Yuniar Larasati (Universitas Batanghari Jambi, 2026)
This study aims to analyze the effectiveness of tax learning methods among Accounting students at Universitas Jenderal Achmad Yani. It compares the 2021 cohort, who completed Taxation 1 and 2 courses, with the 2022 cohort, who directly joined tax certification (brevet) without theoretical coursework. Employing a descriptive qualitative approach, data were collected through in-depth interviews and analyzed thematically. The findings indicate that theoretical learning provides a solid conceptual foundation, enhancing students’ comprehension and readiness for practical content. In contrast, students without prior theory faced difficulties in understanding tax concepts, terminology, and case resolution. The study highlights the importance of a hybrid approach integrating theory and practice to foster comprehensive tax competence. These findings contribute to curriculum policy formulation under the Merdeka Belajar Kampus Merdeka (MBKM) framework.